Sosialisasi Penanggulangan Bencana Perspekti Islam Dalam Meningkatkan Kepedulian Mahasiswa terhadap Lingkungan - Marlina, Lilis; Luthfi, Luthfi; Erliana, Hilma (Universitas Teuku Umar, 2024)
Islam as the religion of rahmatan lil a'alamin has a unique concept in disaster management and is different in disaster management based on contemporary concepts in the initial steps in responding to disasters. Understanding the concept of disaster management is a very important aspect to maintain environmental balance by reducing disaster risk. The aim of this service activity is to increase students' knowledge and skills regarding disaster management from a contemporary and Islamic perspective, as well as increasing students' awareness of the environment as an effort to reduce disaster risk. This effort is carried out by carrying out socialization activities on disaster management from an Islamic perspective to make students care about the environment. Based on the results of this socialization activity, participants understood the material presented by 85%. Socialization about disaster management from an Islamic perspective can be a solution to the weaknesses of disaster management in contemporary concepts.